Sex and Ethnic Disparities during COVID-19 Pandemic among Acute Coronary Syndrome Patients - Abdulmajeed Alharbi; Ahmed Elzanaty; Mohammad Safi; Momin Shah; Halah Alfatlawi; Zachary Holtzapple; Abed Jabr; Ehab Eltahawy (Hearts, 2024)
Introduction: The Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) caused a global pandemic that emerged in 2019. During this period, a significant disparity in hospitalization and mortality rates emerged, particularly in terms of Ethnicity and sex. Notably, this study aims to examine the influence of sex and Ethnicity on acute coronary syndrome outcomes, specifically during the global SARS-CoV-2 pandemic. Methods: This retrospective observational study analyzed adult patients hospitalized with a primary diagnosis of acute coronary syndrome in the United States in 2020. Primary outcomes included inpatient mortality and the time from admission to percutaneous coronary intervention (PCI). Secondary outcomes encompassed the length of stay and hospital costs. The National Inpatient Sample (NIS) database was utilized to identify and study patients in our test group. Results: A total of 779,895 patients hospitalized with a primary diagnosis of acute coronary syndrome in the year 2020 and 935,975 patients in 2019 were included in this study. Baseline findings revealed that inpatient mortality was significantly higher in 2020 compared to 2019, regardless of sex and Ethnicity (adjusted odds ratio (aOR) 1.20, 95% confidence interval (CI) 1.12–1.23, p-value < 0.001). Concerning primary outcomes, there was no difference in inpatient mortality for hospitalized patients of different sexes between 2019 and 2020 (STEMI: aOR 1.05, 95% CI 0.96–1.14, p-value 0.22; NSTEMI/UA aOR 1.08, 95% CI 0.98–1.19, p-value 0.13). Regarding time to admission for PCI, NSTEMI/UA cases were found to be statistically significant in female patients compared to males (mean difference 0.06 days, 95% CI 0.02–0.10, p-value < 0.01) and African Americans compared to Caucasians (mean difference 0.13 days, 95% CI 0.06–0.19, p < 0.001). In terms of the length of stay, female patients had a shorter length of stay compared to males (mean difference −0.22, 95% CI −0.27 to −0.16, p-value < 0.01). Conclusions: As acute coronary syndrome is an urgent diagnosis, a global pandemic has the potential to exacerbate existing healthcare disparities related to sex and Ethnicity. This study did not reveal any difference in inpatient mortality, aligning with studies conducted prior to the pandemic. However, it highlighted significantly longer treatment times (admission to PCI) for NSTEMI/UA management in female and African American populations. These findings suggest that some disparities may have diminished during the pandemic year, warranting further research to confirm these trends in the years to come.